Pratiques d’utilisation des pesticides en agriculture maraîchère de bas-fonds dans la ville de Yaoundé - Georges Yannick Fangue-Yapseu; Marina Awa Ntapnze-Mouliom; Romaric Armel Mouafo-Tchinda (VertigO)
The present study analyses, through a survey carried out among 167 market gardeners from marshy shallows in the city of Yaoundé (Cameroon), some aspects of the use of synthetic pesticides, and the perception of the use of wild plant extracts in the fight against crop’s pests and diseases. The descriptive analysis of the data shows that 85% of the market gardeners surveyed have not been trained in agriculture, and 59% have not received advice on the use of synthetic pesticides. Moreover, only 29% of them have a university education. As a result, even though they claim to know that synthetic pesticides are dangerous to health (97%), they do not comply with good phytosanitary practices and show many symptoms such as stinging nose, fatigue, and watery eyes. However, it is generally known that wild plant extracts can be used to protect crops against the risks associated with pests and parasites. However, only 43% often use it due to lack of money for the purchase of synthetic pesticides (71%). In addition, 66% of them believe that wild plant extracts are not likely to replace synthetic pesticides in agriculture. Thus, this study highlights the problem of orienting approaches to crop protection towards the path of ecology.